2015
DOI: 10.3109/02699052.2014.983978
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in athletic concussion

Abstract: This review applies literature on sleep following traumatic brain injury and concussion to sport concussions and places these considerations in the context of sleep and athletic performance. It also includes a description of sleep abnormalities in sleep duration, quality and timing as well as recommended treatment approaches. Finally, it includes a brief discussion of emerging paradigms of sleep and concussion recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 48 publications
0
25
0
4
Order By: Relevance
“…Of course, there is a great deal of overlap between these symptom clusters, with bidirectional interactions making it difficult to discern causality (e.g., disturbed sleep can both cause and be caused by headaches and irritability). Importantly, the centrality of sleep to mTBI is further evidenced in recovery, with sleep-related processes being increasingly implicated in the neuroplastic recovery from postmTBI symptoms [14].…”
Section: Mild Tbimentioning
confidence: 99%
“…Of course, there is a great deal of overlap between these symptom clusters, with bidirectional interactions making it difficult to discern causality (e.g., disturbed sleep can both cause and be caused by headaches and irritability). Importantly, the centrality of sleep to mTBI is further evidenced in recovery, with sleep-related processes being increasingly implicated in the neuroplastic recovery from postmTBI symptoms [14].…”
Section: Mild Tbimentioning
confidence: 99%
“…poorer sleep has been reported for individual sports like cycling compared team sports like football and basketball) (Lastella et al 2015). Concussion has been associated with disrupted sleep, suggesting professional American football players and other collision sport athletes at risk for brain trauma may also be at greater risk of adverse outcomes secondary to sleep deprivation (Jaffee et al 2015). In the previously described Schwenk survey study of retired American football athletes, individuals reporting both high levels of depression and chronic pain were 32 times more likely to report trouble sleeping as “very common,” which was the most significantly elevated risk of all transition to retirement problems investigated (Schwenk et al 2007).…”
Section: Sleep Disturbancesmentioning
confidence: 99%
“…Sleep disturbances are reported in 30% to 80% of individuals following a concussion and range from an increased need for sleep (hypersomnia) to difficulty falling asleep or maintaining sleep (insomnia) . Insomnia is a highly prevalent symptom following concussion that can last for months after injury . Sleep disturbances can be due to axonal damage that occurs during the concussive injury resulting in dysregulation of the sleep and arousal centers in the brain, including the suprachiasmatic nucleus, hypothalamus, retino‐hypothalamic tract, and the reticular activating system .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that sleep disturbances may be related to poorer recovery following a concussion. Cross‐sectional studies have shown that sleep impairments following a concussion have been strongly associated with increased headache, dizziness, decreased cognitive performance, and return to work . In addition, adequate sleep duration and quality have been shown to be important for immune function, pain modulation, tissue repair, cognitive function, and cardiovascular, metabolic, and neurologic health.…”
Section: Introductionmentioning
confidence: 99%